Association of Grip Strength with Quality of Life in the Chinese Oldest Old - Xie, Boqin; Ma, Chenjuan (International journal of environmental research and public health, 2021)
Emerging studies have suggested an association between grip strength and health-related quality of life (QOL). However, evidence for which specific domains of QOL are associated with grip strength remains limited and inconsistent. Particularly, such evidence is scarce in the oldest old, who constitute one of the most vulnerable populations. This cross-sectional study aimed to examine the association between grip strength and overall QOL as well as specific domains in the oldest old. It included 400 community-dwelling older adults aged 80 years or older from Shanghai, China. QOL was assessed using the WHO Quality of Life of Older Adults instrument, and grip strength was measured using a digital spring-type dynamometer. On average, the overall QOL score was 54.68 (SD = 12.05). Estimates of risk-adjusted linear regressions indicated that higher grip strength was associated with better overall QOL (β = 4.40, p < 0.001) as well as the domains of autonomy (β = 6.74, p < 0.001); fulfillment with past, present, and future activities and achievements (β = 3.52, p = 0.004); and satisfaction with social participation (β = 6.72, p < 0.001). Our findings highlight the importance of maintaining or improving grip strength in delaying or reducing the decline in QOL among the community-dwelling oldest old. Also noteworthy is that the associations between grip strength and specific domains of QOL in the oldest old vary.